Assessing CRM strategies and their effect on customer satisfaction in Johor’s hospitality industry - Abu Seman, Noor Aslinda; Mohd Fauzi, Nurul Hafizah; Mohamad, Arifha (UiTM Press, 2025)
Customer satisfaction is a critical challenge in the hospitality industry, where hotels face rising consumer expectations and intense competition. While Customer Relationship Management (CRM) offers a strategic solution, many hotels underutilise CRM dimensions—customer orientation, CRM organisation, knowledge management, and technology-based CRM—limiting their ability to enhance guest experiences. This study investigates the effect of CRM dimensions on customer satisfaction in Johor hotels. This study employed a quantitative, correlational, and cross-sectional survey design and successfully collected data from 200 hotel clients in Johor. Convenience sampling targeted guests who had visited Johor hotels within the past three months. Data were analysed using SPSS version 29.0, and multiple regression was applied to examine the relationships between CRM variables and customer satisfaction. The results show that CRM organisation is the most potent positive driver of customer satisfaction, emphasising the importance of well-structured CRM practices in improving customer experiences. Technology-based CRM also significantly impacts satisfaction, highlighting technology’s growing role in hotel operations. However, customer orientation and knowledge management negatively affected satisfaction, suggesting misalignments between hotel practices and customer expectations. These findings provide valuable insights for hotel management, urging a focus on enhancing CRM organisation and leveraging technology while reassessing customer orientation and knowledge management strategies. This study contributes to CRM research, extending customer experience theory and supporting elements of the Expectancy-Disconfirmation Theory. It calls for an integrated approach to CRM implementation and offers recommendations for future research to explore the adverse effects of specific CRM dimensions and regional differences in customer satisfaction.